Status report on novel intraoral scanner-based registration method of axes of rotation of the mandible: Proof of potential applicability and technological glass ceiling of in-house development - Laura Lengyel; Balazs Laczi; Antal Nagy; Emil Segatto; Gergo Balazs; Arpad Safrany-Fark (PLoS ONE, 2026)
A fast, equipment- and radiation-free input methodology for digital articulation is desirable for basic dental and surgical procedures of relatively low complexity. Our team previously proposed an intraoral scanner (IOS)-based strategy for calculating the mandibular axis of rotation using dual bite registrations in open and closed positions. In this study, we aimed to develop a methodology for validating this registration system using a state-of-the-art jaw motion tracking device (Modjaw). The bite alignment accuracy of the scanner used ( Medit i600 ) proved sufficient for the task; however, its technical settings allow processing of only a limited number of bite positions, thereby restricting the number of cases that can be analysed. While in-house, insoluble technical limitations restricted the number of participants to four, significantly limiting the generalizability of the results, several main trends nevertheless appear to emerge: We verified our previous results regarding the error-induced effect ratios (EcD and AEcFE) and provided strong in-vivo support for our earlier in-vitro findings. Notably, alignment of axes obtained with our IOS-based method closely resembled the “ parallel error direction ” described previously. The reproducibility of our methodology approaches the desired 0.1 mm error threshold, but when compared with our control tool (Modjaw), it does not yet meet this criterion. The level of inaccuracy suggests that the goal remains achievable; with protocol modifications, the method could become an acceptable alternative for virtual articulation. Our findings highlight persistent clinical dilemmas and underline that many patient safety concerns remain unresolved, even in the era of advanced digital technologies. We proposed a renewed digital version of the conventional analogue control setup of articulation methods by dynamic motion registers, as a potential strategy to establish and maintain patient safety standards. Although integrating different digital platforms poses significant technological challenges, automated metrics and comparative setups offer advanced possibilities compared to the analogue experimental era.